0005 The Effect Of Chemogenetic Silencing Of Corticotropin Releasing Factor Neurons In The Paraventricular Nucleus On Post-stress Sleep In Mice. (12th April 2019) - Gvilia, Irma; Kumar, Sunil; McGinty, Dennis; Szymusiak, Ronald
Abstract: Introduction: We have previously shown that pharmacological elevation of corticotropin releasing factor (CRF) signaling in the brain results in exacerbation of sleep disturbances evoked by the exposure of rats to the dirty cage of a male conspecific. In this study, we examined the effect of chemogenetic silencing of CRF neurons in the hypothalamic paraventricular nucleus (PVN) on sleep occurring after the exposure of mice to dirty cages from male rats. Methods: To achieve Cre-dependent expression of hM4Di inhibitory DREADDs (designer receptors activated by designer drugs), a group of CRF-ires-cre male mice (n=5) received bilateral injections of AAV-hSyn-DIO-hM4Di-mCherry targeting the PVN. The other group of CRF-ires-cre mice (n=4) was injected AAV-hSyn-DIO-mCherry (control vector). All mice were implanted with EEG/EMG electrodes. Dirty cage experiments were started following a 4-week postsurgical period to allow gene recombination and expression. Mice were subjected to intraperitoneal (IP) administration of clozapine-n-oxide (CNO; 3 mg/kg) at ZT1, placed into dirty cages, and recorded for post-stress sleep. Results: In mice expressing hM4Di inhibitory DREADDs versus mice injected with control AAV, IP CNO (3 mg/kg) resulted in a significant decrease of post-stress sleep onset latency, decrease of time spent in wakefulness (first hour, 76±5.5 vs. 88±11.3, second hour, 39.4±10.5% vs. 80.4±9.9%; third hour, 42.3±3.5% vs. 46.4±16.5%; fourth hour, 46.4±6.6 vs. 54.6±10.9), and increase in non-rapid eye movement (NREM) sleep time (23.8±5.6% vs. 11.9±11.3%; 59.3% ±9.7 vs. 19.6 ± 9.9%; 56.2±3.1% vs. 51.4±14.7%; 52.5±6.6 vs. 44.9.4±11.4). The hM4Di expressing mice exhibited longer episodes of NREM sleep, compared to mice injected with control AAV (first hour, 131.3±80.4sec vs. 19±1.9sec; second hour, 437.6±85.7sec vs. 77.8±45.4sec; third hour, 467.5±142.8sec vs. 142±82.7sec; fourth hour, 230.3±86.6sec vs. 194±74.9sec). Conclusion: Chemogenetic silencing of CRF neurons in the PVN attenuates acute stress-induced sleep disturbance in mice. Support (If Any): Department of Veterans Affairs Merit Review Grant # BX00155605